PATTERNS OF CHICKEN MEAT AND EGG CONSUMPTION IN RURAL HOUSE HOLDS OF JAGITIAL DISTRICT OF TELANGANA STATE - SWATHI BORA, SRINIVAS GURRAM, V.CHINNI PREETAM and (The Journal of Research, PJTSAU, 2019)
The consumption patterns of chicken meat and egg was studied in Jagitial district of Telangana on a sample size of 300 households. The results of the study concluded that most of the population is consuming chicken meat when compared to mutton, pork and fish. Majority of the respondents consuming 1 kg broiler meat/household/time and 3-5 eggs/ household/time.Â  Majority of the respondents were spending 100-250 rupees for purchasing chicken meat/household/time. Majority of the households preferred chicken curry as utilization product followed by fry, biryani and kheema. Most of the people do not know the nutritive value of meat and egg.